BODY MASS STATUS OF SCHOOL CHILDREN OF DERA ISMAIL KHAN, PAKISTAN - Ramzan, Muhammad; Ali, Irshad; Khan, Abdus Salam (Journal of Ayub Medical College Abbottabad, 2008)
Background: Childhood obesity is a global epidemic involving both developed and developing countries. It is a stare of over-nutrition with long term complications such as dyslipidemia, hypertension, and coronary artery disease and type-2 diabetes. Underweight is the result of under nutrition leading to reduction in growth and development of every body organ especially the Central Nervous System. Long term under-nutrition causes failure in linear growth (height) of the child. Growth is further retarded by the repeated attacks of respiratory infections, diarrhea and anemia as a result of reduced immunity. Methods: This study was carried out eight primary schools of Dera Ismail Khan (Private, semi government organizations, and welfare foundations) having mixed population with some of the wards belonging to high socioeconomic group. Thorough clinical examination excluded those suffering from chronic heath problems. Height and weight of each one was taken body mass index of determined according to '˜Quatelet's' index. Body mass index number was plotted on the CDC S age and gender specific growth charts 2-20 years for BMI-for age percentile and body mass status (underweight, normal weight, overweight/at the risk of overweight and obese/overweight. Results: Total 1338 school going children (6- 11years) were examined with 865 (67.75%) boys and 471 (35.25%) as girls. 13.39%, 72.15%, 8.83% and 5.61% as underweight, normal weight, overweight and obese respectively. Percentage of underweight was higher in girls (25%) than boys (13.22). Percentage of obesity was higher (5.17%) in boys than girls (1.39%). Conclusion: Awareness about balanced diet, improvement in the level of education and socioeconomic conditions, easy access to health facilities and prevention of the gender discrimination, are the remedial measures to be taken to redress the situation. Keywords: Children, Height, Weight, Body mass index.